(untitled) (Annals of Medical Research, 2026)
Aim: Hemoptysis is defined as expectoration of blood from the lower respiratory tract, whereas pseudohemoptysis is defined as bleeding originating from the upper airways or gastrointestinal tract. Distinguishing between these entities in children is essential because of their differing clinical implications. This study aimed to assess the diagnostic value of clinical features in differentiating hemoptysis from pseudohemoptysis in pediatric patients and to analyze the underlying causes and diagnostic approaches. Materials and Methods: A retrospective review was conducted on 94 pediatric patients who presented with oral bleeding between January 2018 and December 2024. We analyzed data on demographics, bleeding characteristics, clinical findings, diagnostic imaging, and etiologies. Results: Hemoptysis was diagnosed in 51% (n = 48) and pseudohemoptysis in 49% (n = 46) of the cases. Cough, sputum production, and pink-to-bright red blood cells were significantly associated with hemoptysis (p<0.05). In contrast, pseudohemoptysis was more often associated with blood mixed with saliva, which came directly from the mouth. Fever and purulent sputum were more frequent in the hemoptysis group. Abnormal chest X-ray and CT findings were significantly more common in patients with hemoptysis. The leading causes of hemoptysis were parenchymal lung diseases (58.3%) and idiopathic causes (29.2%), whereas pseudohemoptysis was mainly caused by upper respiratory tract conditions, such as adenoid hypertrophy and sinusitis (24.2%), idiopathic etiologies (21.7%), and artificial bleeding (8.8%). Conclusion: In children, only half of the cases presenting with blood in the mouth are true hemoptysis. The most important diagnostic indicators of hemoptysis are bright red to pink color, accompanying cough, and any suspicious findings on chest radiography. The most common underlying causes of hemoptysis and pseudohemoptysis are lower and upper respiratory tract infections, respectively.